2014
DOI: 10.1111/mmi.12861
|View full text |Cite
|
Sign up to set email alerts
|

Role of the aminotransferase domain in Bacillus subtilisGabR, a pyridoxal 5′‐phosphate‐dependent transcriptional regulator

Abstract: SummaryMocR/GabR family proteins are widely distributed prokaryotic transcriptional regulators containing pyridoxal 5′-phosphate (PLP), a coenzyme form of vitamin B6. The Bacillus subtilis GabR, probably the most extensively studied MocR/GabR family protein, consists of an N-terminal DNA-binding domain and a PLP-binding C-terminal domain that has a structure homologous to aminotransferases. GabR suppresses transcription of gabR and activates transcription of gabT and gabD, which encode γ-aminobutyrate (GΑΒΑ) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
67
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(72 citation statements)
references
References 24 publications
5
67
0
Order By: Relevance
“…The DB‐(linker included) and the AAT‐like domains were separately expressed and purified as soluble proteins, suggesting that each domain is an independent folding unit . Differential scanning calorimetry, sedimentation velocity and gel filtration analyses showed that GabR is a dimer . The shape of GabR in solution, determined by small angle X‐ray scattering (SAXS), is also consistent with its dimeric crystal structure .…”
Section: The Chimeric Structure Of Mocr‐tfsmentioning
confidence: 71%
“…The DB‐(linker included) and the AAT‐like domains were separately expressed and purified as soluble proteins, suggesting that each domain is an independent folding unit . Differential scanning calorimetry, sedimentation velocity and gel filtration analyses showed that GabR is a dimer . The shape of GabR in solution, determined by small angle X‐ray scattering (SAXS), is also consistent with its dimeric crystal structure .…”
Section: The Chimeric Structure Of Mocr‐tfsmentioning
confidence: 71%
“…1A). A search of the Conserved Domain Database (CDD) (http://www.ncbi.nlm.nih.gov/Structure/cdd/cdd.shtml) revealed that the predicted gene product, EhuR, belongs to the MocR/GntR subfamily, members of which have been reported to be transcriptional regulators (3,4,7,8). Similar to other MocR proteins described previously, EhuR is predicted to consist of an N-terminal helix-turn-helix DNA-binding domain and a C-terminal domain with homology to members of the aspartate aminotransferase superfamily.…”
Section: Resultsmentioning
confidence: 99%
“…Bioinformatic analysis revealed that ehuR belongs to the MocR family, which has a characteristic structure, i.e., an N-terminal HTH DNA-binding domain and a C-terminal domain with homology to members of the aspartate aminotransferase superfamily (3). These proteins require the cofactor PLP to catalyze the reversible transfer of an amino group from an amino acid to an acceptor (8,13,14). Members of the MocR family can be found in both Gram-negative and Gram-positive bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…The band at 425 nm may be attributed to the ketoenamine form of either PLP or PL covalently bound to bcPdxR as a Schiff base with a lysine residue [23]. The band at 335 nm arguably corresponds to the enolimine form of the same Schiff base, as indicated by the presence of emission bands at 400 and 500 nm when the protein was excited at 335 nm (data not shown) [24] and similarly to GabR from B. subtilis [25]. Treating the protein with hydroxylamine [26], we could obtain an apo-form of PdxR, in which the bands at 335 and 425 nm had disappeared (Fig.…”
Section: B Clausii Pdxr Activates Transcription Of the Pdxst Operonmentioning
confidence: 99%